Updating Clinical Practice Guidelines for the Management of Chronic Pain: A Systematic Review - Ellar Yury; Anne Marl (Journal of Midwifery History and Philosophy, 2025)
Background: Chronic pain is a prevalent and debilitating condition affecting millions worldwide. With advancements in medical research and treatment modalities, there is a continuous need to update clinical practice guidelines (CPGs) to ensure optimal patient care. The frequent emergence of new evidence necessitates systematic updates to CPGs to maintain their relevance and efficacy. Objective: This systematic review aims to identify, evaluate, and summarize the latest updates in CPGs for the management of chronic pain, providing healthcare professionals with evidence-based recommendations to enhance patient outcomes. Methods: A comprehensive literature search was conducted across multiple databases, including PubMed, MEDLINE, and Cochrane Library, from January 2015 to December 2023. Inclusion criteria were studies that focused on updated CPGs for chronic pain management, written in English, and published in peer-reviewed journals. Data extraction was performed independently by two reviewers, and discrepancies were resolved by consensus. The quality of guidelines was assessed using the AGREE II instrument. Results: The review identified 32 updated CPGs across various chronic pain conditions, including neuropathic pain, fibromyalgia, and chronic low back pain. Key updates include the recommendation of multimodal approaches, incorporating pharmacological and non-pharmacological treatments, patient-centered care, and the importance of individualized treatment plans. Notably, recent guidelines emphasize minimizing opioid use and increasing the use of non-opioid analgesics and complementary therapies. Conclusion: The updated CPGs reflect a paradigm shift towards a more holistic and individualized approach in managing chronic pain. These guidelines underscore the importance of integrating patient preferences and multidisciplinary strategies. The findings of this review highlight the need for continuous education and training for healthcare providers to align with the evolving standards of chronic pain management.